Drug-Coated Balloon Versus Standard Percutaneous Transluminal Angioplasty for the Treatment of Superficial Femoral and Popliteal Peripheral Artery Disease: 12-Month Results From the IN.PACT SFA Randomized Trial. Issue 5 (3rd February 2015) - Tepe, Gunnar; Laird, John; Schneider, Peter; Brodmann, Marianne; Krishnan, Prakash; Micari, Antonio; Metzger, Christopher; Scheinert, Dierk; Zeller, Thomas; Cohen, David J.; Snead, David B.; Alexander, Beaux; et al.
Abstract : Background—: Drug-coated balloons (DCBs) have shown promise in improving the outcomes for patients with peripheral artery disease. We compared a paclitaxel-coated balloon with percutaneous transluminal angioplasty (PTA) for the treatment of symptomatic superficial femoral and popliteal artery disease. Methods and Results—: The IN.PACT SFA Trial is a prospective, multicenter, single-blinded, randomized trial in which 331 patients with intermittent claudication or ischemic rest pain attributable to superficial femoral and popliteal peripheral artery disease were randomly assigned in a 2:1 ratio to treatment with DCB or PTA. The primary efficacy end point was primary patency, defined as freedom from restenosis or clinically driven target lesion revascularization at 12 months. Baseline characteristics were similar between the 2 groups. Mean lesion length and the percentage of total occlusions for the DCB and PTA arms were 8.94±4.89 and 8.81±5.12 cm ( P =0.82) and 25.8% and 19.5% ( P =0.22), respectively. DCB resulted in higher primary patency versus PTA (82.2% versus 52.4%; P <0.001). The rate of clinically driven target lesion revascularization was 2.4% in the DCB arm in comparison with 20.6% in the PTA arm ( P <0.001). There was a low rate of vessel thrombosis in both arms (1.4% after DCB and 3.7% after PTA [ P =0.10]). There were no device- or procedure-related deaths and no major amputations. Conclusions—: In this prospective, multicenter, randomized trial, DCB was superior to PTA and had a favorable safety profile for the treatment of patients with symptomatic femoropopliteal peripheral artery disease. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique Identifiers: NCT01175850 and NCT01566461. Abstract : Supplemental Digital Content is available in the text.